Ethical Leadership Behaviour Of Heads Of Department And Job Performance Of Academic Staff In South-South Universities, Nigeria - Efanga, Sunday I.; Effiong, Roseline C.; Nwokomah, Joseph M. (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to determine the relationship between ethical leadership behaviour of heads of department and job performance of academic staff in South-South Universities, Nigeria. Three null hypotheses formulated for the study were tested using the simple regression analysis at 0.05 level of significance, 1 and 998 degrees of freedom. The ex-post facto survey design was used. The study population was 739 heads of department and 14,000 academic staff in public Universities in South-South, Nigeria. The multi- stage sampling technique involving stratified sampling and simple random sampling was used to select a sample of 204 heads of department and 1020 academic staff for the study. A researcher made instruments, “Ethical Leadership Behaviour of Heads of Department Questionnaire (ELBHDQ)” and “Job Performance of Academic Staff Questionnaire (JPASQ)” with items measured on 4-point rating scale were used for data collection. The instruments were given to two validates in educational management and educational evaluation in the University of Uyo to determine the validity. The reliability of the instruments was also determined by internal consistency method using the cronbach’s alpha analysis in which coefficients of 0.76 and 0.82 showed that the instruments were reliable. All the three hypotheses were rejected since the calculated F-values of 15.19, 6692.30 and 2333.33 were greater than the critical F-value of 3.84 thus indicating that there was a significant relationship between ethical leadership behaviour of heads of department and job performance of academic staff in South-South Universities in Nigeria. It was concluded that management should maintain high ethical standards in the Universities so that the employees’ job performance would improve. Among the recommendations was that the University management should enforce disciplinary actions against unethical conduct. Indiscipline staff with clear cases of misconduct should be sanctioned or sacked.